Questions and answers on parenting a handbook for parents, teachers, and everyone involved with children - Tan, Emma R. (Bookmark, 1995)
Purpose: This book provides "collections of factual situations covering early childhood, adolescence, marital and extramarital episodes, the single parent and coping with the death of a child."